Psychological Well-Being of Parents in Assisting Children in Online Learning : Phenomenological Study of Parents with ADHD Children in Late Childhood - Santi Putu (Balitbangda Provinsi Jambi, 2022)
Online learning events carried out for students with ADHD certainly cause children to experience more difficulties, but parents also experience complex problems in assisting children's online learning during Covid-19. According to Ryff, mental well-being consists of six distinct dimensions. This study aims to determine the mental well-being of parents of ADHD children aged 6-12 years who are undergoing online learning based on Ryff's theory. This study uses a qualitative research design. The results of this study indicate that the parents' condition of mental well-being is quite low. Parents are still able to organize and make decisions when there is online learning. However, online learning affects the acceptance of their situation, fosters good relationships with others, manages and takes advantage of existing opportunities, sees the meaning of experiences before and after accompanying children to learn online and is not aware of their potential.